PENETAPAN ORIENT SEBAGAI CALON BUPATI SABU RAIJUA UU NO 8 TAHUN 2015 - Relliano Yopaca Fajrul Falaakh; Tri Sulistyowati (Reformasi Hukum Trisakti, 2022)
The procedure for holding regional elections, which is expressly outlined in the law and runs from the registration stage to the inauguration stage, is undoubtedly not a guarantee for the smooth operation of democracy during the holding of regional elections. The issue is formulated as to what the Law No. 1 of 2015's requirements and procedures are for selecting candidates for regents, as well as what the Law No. 12 of 2006's citizenship provisions mean for the Orient Patriot Riwu Kore and the implications of those provisions for his selection as a candidate for regent. Research technique using secondary legal normative data. Deductive logic is used to draw conclusions after a qualitative analysis of the data. The findings of the study, discussion, and conclusion show that Orient citizenship status, which has two (two) nationalities, has been automatically lost and to be determined as a candidate for regent null and void. This is based on the most important requirements for running for office, namely being an Indonesian citizen and having to fulfill other requirements and procedures in accordance with regulations. It is hoped that the Pilkada will follow the rules and satisfy the demands of the Governor, the Regent, or the Mayor as set forth in Law No. 1 of 2015.